Computers, Computer Technology and the Physically Disabled - Desautels, E.J. (University of Wisconsin-Madison Department of Computer Sciences, 1973)
At least 20,000,000 people in the U. S. are afflicted by physical disabilities which interfere with their lives. The number and distribution of disabilities such as visual, hearing and mobility impairments is considered, to motivate an examination of a variety of computer aids for the handicapped. Computerized braille systems are found to be practical and cost-effective, and a variety of devices for embossing braille are described. Research in reading machines for the blind, using voice synthesizers, appears to be proceeding rapidly. The need for large print (large type) output has not generally been sufficiently emphasized, and the use of electrostatic printers is suggested as a possible output device. A computer-independent device, the Optacon, which provides tactile input to the blind is currently in use, and is especially helpful to blind programmers. The deaf use teletypewriters and acoustic couplers to communicate via the telephone network. Intelligent typewriters, and automated letter boards are practical alternative methods of communication for some people with motor impairments. Ignorance of the needs of the physically disabled can result in operating system designs which present barriers to them.